Trimester two gestational exposure to bisphenol A and adherence to mediterranean diet are associated with adolescent offspring oxidative stress and metabolic syndrome risk in a sex-specific manner - Zamora, Astrid N.; Marchlewicz, Elizabeth; Téllez-Rojo, Martha M.; Burant, Charles F.; Cantoral, Alejandra; Song, Peter X. K.; Mercado, Adriana; Dolinoy, Dana C.; Peterson, Karen E. (Frontiers in Nutrition, 2022)
Background: Exposure to prenatal bisphenol A (BPA) and Mediterranean Diet Score (MDS) has been linked to metabolic risk in child offspring. It remains unclear if independent and interactive effects persist in adolescence. Methods: We examined prenatal BPA and MDS on adolescent offspring metabolic syndrome risk score (MRS) and 8-isoprostane (8-iso), a biomarker of oxidative stress. Data from maternal-adolescent dyads from a Mexico City cohort were utilized, including trimester-specific prenatal BPA from spot urine and MDS from food frequency questionnaires. Offspring socio-demographic data and biomarkers to estimate MRS and 8-iso were obtained during peri-adolescence. Results: Adjusted linear regression models examined associations between trimester-specific BPA, MDS, and BPA*MDS on outcomes. Sex-stratified analyses revealed a significant association between MDS with increased 8-iso (β = 0.064, p < 0.05), and a marginal association between trimester two BPA with increased 8-iso (β = 0.237), while MDS modified the marginal association between BPA and 8-iso in females (β = 0.046). A negative, marginal association was observed between trimester two BPA and MRS (β = -0.728), while BPA*MDS was marginally, positively associated with MRS (β = 0.152) in males. Conclusions: Study findings indicate that trimester two prenatal BPA and maternal adherence to a Mediterranean diet may have sexually dimorphic effects on adolescent offspring oxidative stress and metabolic syndrome risk.